(untitled) (Annals of Medical Research, 2025)
Aim: To investigate proline-rich protein 11 (PRR11) transcription levels and its prognostic effect in early-stage (non-metastatic) bladder cancer. Materials and Methods: Thirty-one patients diagnosed with early-stage (non-metastatic) bladder cancer were included in the study. Tumor tissues of the patients at the time of diagnosis were obtained from the pathology laboratory, PRR11 transcription levels were analyzed, and "median fold change" values ​​for PRR11 transcription levels were obtained. According to the median PRR11 transcription level determined from these values, the patients were divided into two groups (n = 16 and n = 15). The demographic and clinicopathological characteristics of the patients were examined, and the survival outcomes of the two groups were compared. Results: The determined median PRR11 transcription level was 1.386 (range: 0.135- 2.016). In the patient group with a median PRR11 transcription level ≤1.381 (n=16), median disease-free survival (mDFS) was 19 months (95% CI: 2.1-48.4 months); in the group with >1.381 (n=15), mDFS was 11 months (95% CI: 7.5-14.4 months). In the group with ≤1.381, median overall survival (mOS) was 27 months (95% CI: 4.1-58.3 months), and in the group with >1.381, mOS was 14 months (95% CI: 8.1-19.8 months). Conclusion: Our study revealed a negative correlation between PRR11 transcription level and survival outcomes in patients with early-stage bladder cancer. The PRR11 transcription level may be a prognostic marker in patients with early-stage bladder cancer. More comprehensive, prospective, and randomized controlled trials are needed.